2017
DOI: 10.1310/sci16-00003
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Effectiveness of Virtual Reality Game-Based Training on Balance and Functional Performance in Individuals with Paraplegia

Abstract: To determine whether there is any difference between virtual reality game-based balance training and real-world task-specific balance training in improving sitting balance and functional performance in individuals with paraplegia. The study was a pre test-post test experimental design. There were 30 participants (28 males, 2 females) with traumatic spinal cord injury randomly assigned to 2 groups (group A and B). The levels of spinal injury of the participants were between T6 and T12. The virtual reality game-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
72
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(78 citation statements)
references
References 31 publications
6
72
0
Order By: Relevance
“…Participants who had a persistent postural drop in blood pressure were trained first on a tilt table and were included for the study only when asymptomatic. The EG showed significant improvement (p<0.001) in all outcome measures (BBS, POMA-B, and FRS), which have also been reported by some earlier studies [15][16][17].…”
Section: Discussionsupporting
confidence: 86%
“…Participants who had a persistent postural drop in blood pressure were trained first on a tilt table and were included for the study only when asymptomatic. The EG showed significant improvement (p<0.001) in all outcome measures (BBS, POMA-B, and FRS), which have also been reported by some earlier studies [15][16][17].…”
Section: Discussionsupporting
confidence: 86%
“…The scores achieved in the PEDro scale are shown in Table 1 . Six studies had high methodological quality with PEDro scores ≥6: Gil-Agudo et al [ 7 ], D’Addio et al [ 6 ], Dimbwadyo-Terrer et al (2016) (a) [ 2 ], Dimbwadyo-Terrer et al (2016) (b) [ 34 ], Khurana et al [ 35 ], and Prasad et al [ 36 ]. Dimbwadyo-Terrer et al (2013) [ 11 ] scored 5, achieving the lowest score.…”
Section: Resultsmentioning
confidence: 99%
“…Concerning the assessment of the risk of bias for each of the studies included in this review, the researches carried out by Dimbwadyo-Terrer et al 2016 (a) [ 2 ], Khurana et al [ 35 ] and Prasad et al [ 36 ] had the lowest risk of bias, as shown in Figure 2 . Likewise, regarding the risk of bias among all the included studies, the lowest biases are presented in the incomplete outcome data (0%) and the selective reporting (0%), while the highest percentage (85.5%) was obtained in the allocation concealment, as shown in Figure 3 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations